(3cJGH ajg JbSje GdYdhe hGKHGJ GdMb hcTa Gdecfhfs - (3CHh EHQGgje ESeGYjd Hf eMeO Hf MGeO GdJejejs
(3ChdgG (B:s
(3adGfbhd Ef gPg GdUhQI GdeQjHI gi gh afLYdg eMUhQkG eMOhOkG s
(3BNQgG (B:s
(3aef OYG GdJhMjO hJHQC ef GdJdMjf hYQa Gdehdi Ld PcQg hhMOg HSja ehdGfG SHMGfg hHg GSJYjf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B22s
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV cdeGJgG HGdMeQIs
(3QSGdI ef QSGFd GdOQhR s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds